MODIFICATION OF VOLCANIC ASH OF KELUD AS SELECTIVE ADSORBENT MATERIAL FOR Zn(II) AND Cr(VI) METAL IONS - Susila Kristianingrum; Endang Dwi Siswani; Sulistyani Sulistyani (Jurnal Sains Dasar, 2018)
This research aims to prepare an adsorbent from Kelud volcanic ash for better adsorption efficiency of Zn(II) and Cr(VI) than Kieselgel60GE'Merck. Adsorbent synthesis has been carried out by dissolving 6 grams of volcanic ash, activated at 700 oC for 4 hours and washed with HCl 0.1 M into 200 mL of sodium hydroxide 3 M with stirring and heating at 100 °C for 1 hour. Then, sodium silicate filtrate was neutralized using hydrochloric acid. The mixture was allowed to stand for 24 hours then filtered and washed with aqua DM, then dried and crushed. The procedure was repeated for nitric acid with a contact time of 24 hours. The products were then characterized using FTIR subsequently determined acidity, moisture content, and tested for its adsorption of the Zn(II) and Cr(VI) ions, by using AAS. The results showed that the type of acid that produced highest rendemen is AK-HCl-3M i.e. 25.50%, acidity of the synthesized adsorbent silica gel all have similarities with Kiesel gel 60G E' Merck ie 6.302mmol/g and the water content of the silica gel adsorbent synthesized similar to Kiesel gel 60G E'  Merck i.e adsorbent AK- HCl-3 M. The character of the functional groups of silica gel synthesized all have similarities with Kiesel gel 60G E'Merck as a comparison. Qualitative analysis by FTIR indicates that it has formed a bond of Si-O-Si and Si-OH. The optimum adsorption efficiency of the metal ion Zn(II) obtained from AK-HNO3-3 M adsorbent is equal to 63.24% for electroplating waste and the optimum adsorption efficiency of the Cr(VI) metal ion obtained from the adsorbent AK- HNO3-3M is equal to 64.01% for tannery waste. Keywords: Kelud, Volcanic Ash, Adsorbent